Naming what we know: threshold concepts of writing studies - Adler-Kassner, Linda, author; Wardle, Elizabeth, author; Utah State University Press, publisher (Colorado State University. Libraries, 2015)
Naming What We Know examines the core principles of knowledge in the discipline of writing studies using the lens of threshold concepts"--concepts that are critical for epistemological participation in a discipline. The first part of the book defines and describes thirty-seven threshold concepts of the discipline in entries written by some of the field's most active researchers and teachers, all of whom participated in a collaborative wiki discussion guided by the editors. These entries are clear and accessible, written for an audience of writing scholars, students, and colleagues in other disciplines and policy makers outside the academy. Contributors describe the conceptual background of the field and the principles that run throughout practice, whether in research, teaching, assessment, or public work around writing. Chapters in the second part of the book describe the benefits and challenges of using threshold concepts in specific sites--first-year writing programs, WAC/WID programs, writing centers, writing majors--and for professional development to present this framework in action. Naming What We Know opens a dialogue about the concepts that writing scholars and teachers agree are critical and about why those concepts should and do matter to people outside the field.--Provided by publisher.
Keywords: English language -- Rhetoric -- Study and teaching; Creative writing -- Study and teaching; Academic writing -- Study and teaching